2012
DOI: 10.1121/1.3699266
|View full text |Cite
|
Sign up to set email alerts
|

Temporal predictions based on a gradual change in tempo

Abstract: Previous studies investigating sensitivity to step changes in tempo and prediction of tone onset time have generally utilized isochronous sequences. This study investigates subjects' ability to detect deviations from a gradual change in the tempo of a tone sequence (experiment 1) and their judgment of the perceptually optimal timing of this tone (experiment 2). In experiment 1, inter-onset-intervals within pairs of eight-tone sequences followed a geometric progression to create a gradual tempo change. In one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…That such attentional focus may only be needed for relatively localized parts of a signal is compatible with evidence for the ubiquity of rapid, repeated, apparently unconscious and (in the case of interaction) mutual adjustments of phase rather than period, for cerebellar and (dorsal) thalamo-cortical oscillatory cycles, tapping behaviour and discrimination of 'out of time' events (e.g. [116,117]). An appealing aspect of this interpretation is rstb.royalsocietypublishing.org Phil.…”
Section: Discussionsupporting
confidence: 53%
“…That such attentional focus may only be needed for relatively localized parts of a signal is compatible with evidence for the ubiquity of rapid, repeated, apparently unconscious and (in the case of interaction) mutual adjustments of phase rather than period, for cerebellar and (dorsal) thalamo-cortical oscillatory cycles, tapping behaviour and discrimination of 'out of time' events (e.g. [116,117]). An appealing aspect of this interpretation is rstb.royalsocietypublishing.org Phil.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, Geiser and Kaelin-Lang (2011) demonstrated no impairment of beat detection in a cohort of patients with early Parkinson's disease, regardless of whether they were tested before or after administration of dopaminergic medication (this changed only reaction time). Other psychophysical studies have demonstrated that healthy individuals are unable to prevent themselves from entraining to a rhythmic visual cue ( Rohenkohl, Coull, & Nobre, 2011 ), or to fully adapt their predictions of tone onset time to account for changing temporal context ( Cope, Grube, & Griffiths, 2012 ). Taken together with the present findings, the available data suggest that temporal prediction within a beat-based context crucially relies upon the striatum, and that executive control of this process is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which higher-order sequences are used in predicting subsequent events or INIs is debated. Humans perform poorly at detecting temporal structure in mildly complex patterns (Cope et al, 2012). Finding regularity across a number of intervals correlates with reading ability, while detecting gradual speeding-up/slowing-down does not (Grube et al, 2014).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…However, exposure to strong temporal irregularities can make humans perceive regular events as irregular (Rhodes and Di Luca, 2016). Mildly regular—predictable though non-isochronous—patterns are perceived quite well, possibly based on local properties of the pattern (Cope et al, 2012). In any case it seems that human perception of rhythm is not simply a matter of determining time intervals between acoustic intensity peaks, but that it involves a more complex process, potentially integrating multiple prosodic cues such as pitch, duration, INI or intensity values.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%